2021
DOI: 10.3390/rs13163054
|View full text |Cite
|
Sign up to set email alerts
|

Semantic Segmentation of Tree-Canopy in Urban Environment with Pixel-Wise Deep Learning

Abstract: Urban forests are an important part of any city, given that they provide several environmental benefits, such as improving urban drainage, climate regulation, public health, biodiversity, and others. However, tree detection in cities is challenging, given the irregular shape, size, occlusion, and complexity of urban areas. With the advance of environmental technologies, deep learning segmentation mapping methods can map urban forests accurately. We applied a region-based CNN object instance segmentation algori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…Remote sensing in combination with machine learning technologies can provide a potentially practical and cost‐effective way to study changes in vegetation cover. Results of this study utilizing machine learning methods to UAV images achieved F 1‐scores that are comparable to previous studies of plant segmentation (Elkind et al., 2019; Martins et al., 2021; Torres et al., 2020). Some studies implemented additional information such as digital surface models (DSMs) or multi‐spectral data to classify species to obtain similar or better F 1‐scores (Benjamin et al., 2021; Chabot et al., 2018; Durgan et al., 2020; Husson et al., 2016; Schulze‐Brüninghoff et al., 2021).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Remote sensing in combination with machine learning technologies can provide a potentially practical and cost‐effective way to study changes in vegetation cover. Results of this study utilizing machine learning methods to UAV images achieved F 1‐scores that are comparable to previous studies of plant segmentation (Elkind et al., 2019; Martins et al., 2021; Torres et al., 2020). Some studies implemented additional information such as digital surface models (DSMs) or multi‐spectral data to classify species to obtain similar or better F 1‐scores (Benjamin et al., 2021; Chabot et al., 2018; Durgan et al., 2020; Husson et al., 2016; Schulze‐Brüninghoff et al., 2021).…”
Section: Discussionsupporting
confidence: 87%
“…These techniques can adapt to changing environments and enable ongoing improvement to understand the scene. With the advancement of mapping and computer technologies, DL methods are being tested to identify patterns in the most varied fields of science (Dos Santos Ferreira et al., 2017; Martins et al., 2021; Shen et al., 2017; Torres et al., 2020). Thus far, a large amount of training data are needed to train a DL‐based network for subsequent classification (Goodfellow et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Second, we focus on urban areas, which are relatively under-explored in other work [16,29], although many free data sources exist. Third, existing work relies on strong preprocessing and fully annotated data in which the object has either been accurately delineated [7,20] or been annotated by a bounding box or at least a point label. An example of point labels is done by Ventura et al [30], who manually annotated 100 000 trees from eight cities in the USA and collected multiple years of imagery.…”
Section: Introductionmentioning
confidence: 99%
“…For the segmentation of 2D (Two-Dimensional) images, scholars have tended to use a convolutional neural network in deep learning [16][17][18] from traditional segmentation methods based on edge detection, threshold, region and specific theoretical tools. For example, Martins et al [19] segmented the trees in the urban environment image, Yan et al [20] identified different tree species and Chadwick et al [21] extracted the height of the crown of a single coniferous tree. However, 2D images have problems such as insufficient spatial information and occlusion.…”
Section: Introductionmentioning
confidence: 99%